Introduction: European Social Policy and Society after Brexit: Neoliberalism, Populism, and Social Quality. Issue 1 (January 2019) - Corbett, Steve; Walker, Alan
Abstract : The narrow referendum decision for British exit from the European Union (Brexit), and its explosive political consequences, has become a lens through which decades-long tensions in European society can be viewed. The result, which was expected to be a clear Remain victory, has been interpreted as various combinations of: the unleashing of xenophobic and racist anti-immigrant sentiment; a kick back against disinterested elites by 'left behind' people; the fermenting of nationalist populism by political and media actors; a clash of cultural values; a rejection of 'market is all' globalisation in favour of national borders; or as a reaction against austerity, inequality and insecurity (Corbett, 2016 ; Goodwin and Heath, 2016 ; Hobolt, 2016 ; Inglehart and Norris, 2016 ; Kaufmann, 2016 ; Pettifor, 2016 ; Room, 2016 ; Seidler, 2018 ; Taylor-Gooby, 2017 ). This British-made shock has parallels in and consequences for wider European society. In the Referendum, the EU became an emblematic representation of the distrusted, remote, technocratic elites, who are said to be responsible for an unbelievably large number of societal ills. Meanwhile across Europe there are varieties of Eurosceptic populism and distrust of elites on both the right and left (Ivaldi et al ., 2017 ).